Value Over Technology? Examining the Roles of Perceived Value and Interactive Digital Innovation in Driving Consumer Behavior and Digital Engagement in Retail Markets - Alfina Sitangganga; Darwin Lie; Robet Tua Siregar (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2025)
This study seeks to investigate a consumer behavior model by evaluating the impact of interactive technology-driven digital innovation and perceived value on digital engagement, with customer behavior serving as a mediating variable within the retail sector in Jambi Province. A quantitative research design utilized a survey method with 150 retail consumers as participants. We used Structural Equation Modeling–Partial Least Squares (SEM-PLS) to look at both the measurement and structural models. The findings of the measurement model show that all indicators match the requirements for convergent validity. The outer loading values are all over 0.70, which means that the construct is reliable and valid. The evaluation of the structural model indicates that perceived value exerts a positive and significant influence on both consumer behavior and digital engagement. Also, how people act as consumers has a big effect on how they contact with and participate in digital media. This means that people who think retail services are more valuable are more likely to interact with and participate in digital media. Nevertheless, interactive technology-driven digital innovation does not exhibit a substantial direct impact on customer behavior or digital engagement. These findings suggest that value perception is more influential than technology innovation in determining consumer responses inside digital retail environments. This research enhances the body of knowledge regarding consumer behavior and digital marketing by highlighting the strategic significance of perceived value in augmenting consumer involvement within digital retail contexts.